Domain Walls Conductivity in Hybrid Organometallic Perovskites and Their Essential Role in CH3NH3PbI3 Solar Cell High Performance - Sergey N. Rashkeev (19686943) (2015)
The past several years has witnessed a surge of interest in organometallic trihalide perovskites, which are at the heart of the new generation of solid-state solar cells. Here, we calculated the static conductivity of charged domain walls in n- and p- doped organometallic uniaxial ferroelectric semiconductor perovskite CH3NH3PbI3 using the Landau-Ginzburg-Devonshire (LGD) theory. We find that due to the charge carrier accumulation, the static conductivity may drastically increase at the domain wall by 3 – 4 orders of magnitude in comparison with conductivity through the bulk of the material. Also, a two-dimensional degenerated gas of highly mobile charge carriers could be formed at the wall. The high values of conductivity at domain walls and interfaces explain high efficiency in organometallic solution-processed perovskite films which contains lots of different point and extended defects. These results could suggest new routes to enhance the performance of this promising class of novel photovoltaic materials. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/srep11467